Earnings among Nine Ethnic Minorities and the Han Majority in China's Cities - Björn Anders Gustafsson; Xiuna Yang (Institute for the Study of Labor (IZA), 2016)
This paper asks if economic growth and steps towards a market economy have affected earnings gaps between the Han and nine large urban ethnic minorities: Zhuang, Hui, Manchurian, Tujia, Uighur, Miao, Tibetan, Mongol and Korean. It also asks how earnings premiums and earnings penalties have changed for the nine ethnic minorities. For the analysis we use a subsample of the 2005 China's Inter-Census Survey. We find examples of three different changes over time in earnings premiums and earnings penalties: One ethnic minority for whom the development has been more favourable than for the Han majority; a second category in which development has been similar; and a third category for which development has been unfavourable. We conclude from the analysis that it can be misleading to infer the experience of one ethnic minority from that of another.
Keywords: J15; J31; J71; P23; 330; earnings; ethnic minorities; Uighur; Tibetan; Korean